The Role of Mobile Phone Ownership and Behavioral Factors in Risky Sexual Behavior Among Indonesian Women: Finding from IDHS 2017 - Amin Zakaria; Yuni Asri; Heny Nurma Yunita (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Transmitted infections (STIs) and unintended pregnancies. This study examined sociodemographic, geographic, and behavioral factors, including mobile phone ownership, associated with risky sexual behavior among Indonesian women. A cross-sectional analysis was conducted using data from 30,875 women aged 15–49 years who participated in the 2017 Indonesian Demographic and Health Survey (IDHS). Survey-adjusted multivariable logistic regression was used to identify independent correlates. Compared with women aged 15–20 years, those aged 36–40 years (AOR = 1.47, 95% CI: 1.24–1.78) and ?41 years (AOR = 1.36, 95% CI: 1.16–1.59) had higher odds of risky sexual behavior. Higher educational attainment was also associated with increased odds, including primary education (AOR = 2.11, 95% CI: 1.06–4.22), secondary education (AOR = 2.70, 95% CI: 1.35–5.42), and higher education (AOR = 2.59, 95% CI: 1.28–5.25). Women living in the middle (AOR = 1.72, 95% CI: 1.41–2.10) and western regions (AOR = 1.49, 95% CI: 1.24–1.79), those reporting consistent condom use (AOR = 3.31, 95% CI: 2.93–3.72), those with knowledge of HIV testing (AOR = 1.30, 95% CI: 1.15–1.46), and those owning a mobile phone (AOR = 1.20, 95% CI: 1.04–1.40) were also more likely to report risky sexual behavior. These findings support age-specific, regionally tailored, and digitally supported sexual health interventions to reduce STI risk among Indonesian women.